PENYULUHAN “BULLYING” GUNA PERLINDUNGAN ANAK DALAM TINDAK PIDANA KEKERASAN SISWA SMA NEGERI 1 JAYAPURA - Grisca Valencia Fredrika Walary Ara (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Bullying is a social problem that never ends in society. These problems are found in different social contexts such as education, the world of work, even in everyday life. The perpetrators and victims also come from different age groups. Children and adolescents are a vulnerable age. Meanwhile, school is the most common place where bullying occurs. Sometimes this issue is even internalized with other activities, such as the orientation period for new students. Bullying has become a culture that sometimes students don't realize they take action. So every school needs extensions that can increase students' understanding of bullying. The methods used in this extension are (1) conference; (2) discussion; (3) feedback; and (4) video playback. The results of the counseling show that there is an understanding of students regarding the impact of this treatment which can later make students aware that bullying can occur in various forms. Students can also see the need for their role in reducing cases of bullying (bullying) happened at school.